ASSOCIATION OF PAIN AND OTHER CLINICAL FEATURES WITH DISEASES OF BREAST IN FEAMLES PRESENTING AT TERTIARY CARE HOSPITALS OF SAHIWAL - Shamikha, Waleeja; Makki, Yasir; Zafar, Amjad; Tahir, Qurrat-Ul-Ain; Ikram, Rabia (Pakistan Armed Forces Medical Journal, 2020)
Objective: To find association of clinical features in patients presenting to outdoor patient department with pathologies of breast.Study Design: Cross sectional study.Place and Duration of Study: Sahiwal Medical College Sahiwal, from Oct 2018 to Dec 2018.Methodology: The cross sectional study was conducted at Sahiwal Medical College Sahiwal from 1st Oct 2018 to 31st Dec 2018 after approval from Institutional Review Board of Sahiwal Medical College Sahiwal. The Data was assessed by IBM-SPSS version 22. Significance of the associations was assessed by Fisher’s Exact test.Results: Median age of the female patients with breast related disorders was 27 ± 13. About 53% of the patients were included in mild pain category, 36% in moderate and 11% in severe pain category (table-I). Most of the patients with breast disorders were diagnosed of abscess (35%), mastitis (23%), fibrocystic changes (14%) and fibro adenomas and carcinomas (7% each) (table-II). The association of pain intensity was found out be statistically significant with different breast diseases (p=0.047) (table-III). Almost 49% of the patients presenting with abscess in breast were having mild pain while 71.4% of the patients diagnosed with carcinoma breast were also having mild pain. Of all the cases presented with breast abscess 77% were having non-cyclic breast pain while 23% of these patients were having non-cyclic extra mammary pain.Conclusion: Hence it is concluded that the looking into different intensities of pain and other clinical features in patients can help us in making early diagnosis of pathologies related to breast.